Analisis Sisa Material Besi Tulangan pada Proyek Pembangunan Terminal Tipe B Limboto - Fauzan Lensun; Moh Yusuf Tuloli; Arfan Utiarahman (Transbahasa, 2025)
Reinforcement steel is one of the most expensive materials in building construction projects, accounting for approximately 20%-25% of the total cost. Poor management of this material can lead to significant finansial losses. This research aims to analye the dominant diameters of reinforcement steel that contribute to material waste, estimate the cost of the resulting waste, and identify the factors causing reinforcement steel waste. The research utilized primary data obtained through observation and direct interviews with project implementers, as well as secondary data in the form of shop drawings and budget plans (RAB) to calculate and analyze the percentage of reinforcement steel material waste. The results indicate that the dominant reinforcement steel diameters constributing to material waste based on cost estimation using the Pareto diagram are ribbed steel bars with 19 mm, 16 mm, and 13 mm diameters. The total estimated cost factor contributing to the waste is miscalculation in the estimation of reinforcement volume.